2016
DOI: 10.1080/02755947.2016.1152330
|View full text |Cite
|
Sign up to set email alerts
|

Using Tag‐Return Models to Estimate the Number of Times Fish Are Captured in Fisheries with High Catch‐and‐Release Rates

Abstract: Exploitation rates are often estimated using tag‐return studies. However, in fisheries with a catch‐and‐release component, exploitation rate or fishing mortality may not be the most important metric of interest. Instead, angler catch rates (e.g., fish caught per hour), total catch (including fish that are harvested or released), or the average number of times an individual fish is caught may be a better measure of fishery performance. However, if anglers remove tags from fish before release, then catch estimat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 20 publications
0
7
0
Order By: Relevance
“…To the best of our knowledge, no one has published a method to quantify the increased catch realized through catch‐and‐release fishing. Recycling is often cited as the average number of times each fish is caught (Schill et al 1986; McCormick 2016), but these are estimates of seasonal catchability rather than recycling rate. Proof of recycling exists when catch exceeds abundance, but our methods allow for estimating recycling rate even when catch is well below abundance.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To the best of our knowledge, no one has published a method to quantify the increased catch realized through catch‐and‐release fishing. Recycling is often cited as the average number of times each fish is caught (Schill et al 1986; McCormick 2016), but these are estimates of seasonal catchability rather than recycling rate. Proof of recycling exists when catch exceeds abundance, but our methods allow for estimating recycling rate even when catch is well below abundance.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies counted the number of times tagged fish were reported (Bahr et al 2018; Thorstad et al 2019). Others have combined creel data with population estimates to report the average number of times each fish in the population was caught (Schill et al 1986; McCormick 2016). However, neither of these metrics describes how much catch increased because of multiple recaptures.…”
Section: Introductionmentioning
confidence: 99%
“…Some studies counted the number of times tagged fi sh were reported (Bahr et al 2018 ;Thorstad et al 2019 ). Others have combined creel data with population estimates to report the average number of times each fi sh in the population was caught (Schill et al 1986 ;McCormick 2016 ). However, neither of these metrics describes how much catch increased because of multiple recaptures.…”
Section: Introductionmentioning
confidence: 99%
“…) and allow fisheries managers to monitor the potential impacts of catch‐and‐release angling on fish populations (Pollock and Pine ; Kerns et al. ; McCormick ). Despite the utility of traditional tagging methods, several drawbacks of these techniques exist.…”
mentioning
confidence: 99%
“…Fish tagging and marking techniques are essential tools for understanding population dynamics (Tranquilli and Childers 1982;Pine et al 2012) and allow fisheries managers to monitor the potential impacts of catch-and-release angling on fish populations (Pollock and Pine 2007;Kerns et al 2015;McCormick 2016). Despite the utility of traditional tagging methods, several drawbacks of these techniques exist.…”
mentioning
confidence: 99%